Synthesis of MOF-derived Fe7S8/C rod-like composites by controlled proportion of carbon for highly efficient electromagnetic wave absorption. (March 2021) - Yang, Yunfei; Xu, Dongmei; Lyu, Longfei; Wang, Fenglong; Wang, Zhou; Wu, Lili; Liu, Wei; Liu, Jiurong
Highlights: One-step sulfuration method to construct Fe7 S8 /C composites with different carbon proportion. Analyzing the behaviors of dielectric polarization and synergistic effect of Fe7 S8 and C. Revealing the mechanism of various ratio between Fe7 S8 and C affecting absorbing performance. Abstract: In this study, we firstly used the MOF-derived Fe7 S8 /C rod-like composites as absorbers and systematically investigated the synergistic effect of Fe7 S8 and carbon in electromagnetic wave absorption applications. By controlling the introduced dosage of ferric salt, the proportion of carbon and Fe7 S8 in composites could be adjusted, which made a significant effect on the electromagnetic parameters and absorption performance. When the carbon proportion was about 33.9 wt%, the synergistic effect between Fe7 S8 and carbon guaranteed the optimized impedance matching and strong dissipation ability, presenting superb absorption performance. The optimal performance reflected in the minimum reflection loss of −68.86 dB at 12.08 GHz with a thickness of 1.67 mm, and the effective bandwidth was up to 4.56 GHz at 1.45 mm. Therefore, this study provides a facile method for preparing the Fe7 S8 /C absorbers and emphasizes the significance of the ratios between Fe7 S8 and carbon on the electromagnetic parameters and absorption performance.